Effect of fouling resistance in heat exchanger and the crystal form of CaCO3 in hard circulating cooling water with electrostatic field and alternating current electric field - Jing Xu (IWA Publishing, 2021)
The effect of high voltage electrostatic field and high voltage alternating current electric field on the heat exchanger surface fouling under the conditions of hard water was investigated. The Ca2+ concentration in two water conditions was 12 mmol/L. The Mg2+ concentration was 10 mmol/L and 12 mmol/L respectively. The concentration changed with the Mg2+ concentration. X-ray diffraction and scanning electron microscope results confirmed that the main crystal phases of the scale samples consisted of calcite and aragonite. The high voltage electrostatic treatment can promote scale growth under both water quality conditions. However, the high voltage alternating current electric field treatment shows a good scale inhibition effect under both water quality conditions, and the scale inhibition effect is best when both Ca2+ and Mg2+ concentrations are 12 mmol/L, and the average scale inhibition rate reaches 47.58%. When the calcite content of the scale sample is significantly higher than that of aragonite, Mg2+ affects the growth and solubility of crystals. Conversely, the high voltage alternating current electric field treatment can effectively extend the fouling induction period of the adherent scale on the heat exchanger surface, which is favorable for heat exchanger fouling. HIGHLIGHTS The scale inhibition experiments with different electric fields and Mg2+ concentrations were designed.; Different electric fields have different treatment effects.; The FIP can be used to evaluate the scale inhibition effect.; The HVAC electric field treatment can enhance the inhibition effect of Mg2+ on crystal growth.; After the HVAC electric field treatment, the calcite content in the scale sample increases.;